Pengaruh Gaya Kepemimpinan Terhadap Motivasi Kerja - Fachri Habib; M. Muflih Dermawan; Maidiana Maidiana (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
The purpose of this research is to determine the influence of management style on work motivation and the influence of leadership on organizational behavior. The research method used is library research with a descriptive-qualitative approach. The results of this research show that every manager can determine the direction of an organization. Its limitations are the reason for the formation of organizational or work motivation, the influence of differences in management styles used in management. One of the impacts of this leadership style is that it can influence someone. This effect applies to any workplace or organization. This is because someone usually needs a leadership style in managing a job or an organization. Of course, intermediaries are very important for the functioning of an organization or work, because if an organization or work runs without good management elements from its members and leaders, it will be difficult to resolve all problems that arise in the organization or work quickly and effectively which leads to achieving the goals of the organization's existence, and work satisfaction and motivation to achieve these goals is very low. A leader must have a leadership style, especially social skills and abilities to become a good and responsible leader, and the leader must be truly able to fulfill his responsibilities, exercise control and self-control so that organizational goals are achieved with motivation. manners. a leader's leadership style..